Impact of traffic intensity and vehicular emissions on heavy metal content in vineyard soils, grapes, and wine: a comparative study of two vineyards in South Moravia (Czech Republic) - Prokeš, Lubomír; Hegrová, Jitka; Průšová, Božena; Baroň, Mojmír; Hablovičová, Blanka; Sochor, Jiří; Ličbinský, Roman (Environmental geochemistry and health, 2025)
The primary objective of this study is to evaluate the impact of vehicular traffic emissions on the contamination of wine production by heavy metals. For this purpose, selected heavy elements (As, Ba, Cd, Cr, Cu, Ni, Pb, and Zn) were determined in the samples of vineyard soils, grapes, final wines, and samples from the various phases of the winemaking process of two South Moravian (Czech Republic) vineyards with different intensity of traffic. After the visualisation of the data, the interpretation of the results and risk assessment calculations were performed. The results obtained indicate that contamination of grapes with aerosol is the most important and soil contamination is of minor relevance. The application of fungicides was the primary source of copper and zinc in soils and grapes. During the winemaking process, there is a significant decrease in the content of heavy elements originating from emissions from vehicular traffic. However, winemaking technology was found to be the most important source of heavy elements in the final wine. The health risk assessment indicates a low risk of consumption of both grapes and wine from both the examined and the reference wineries.
Keywords: hodnocení rizik; Grapes; výfukové emise vozidel; Soil Pollutants; monitorování životního prostředí; Heavy metals; Wine; látky znečišťující půdu; Traffic emissions; Vehicle Emissions; Risk Assessment; Wine quality; těžké kovy; Czech Republic; Vineyard soil; Environmental Monitoring; Česká republika; Farms; farmy; Soil; půda; Vitis; Environmental pollution; Metals, Heavy; víno; Comparative analysis